Characteristics of paper made from durian rinds - Masrol, Shaiful Rizal (2013)
Durian rinds where being wasted have potential properties that are suitable to be used as an alternative raw material of cellulosic pulps for papermaking. The physical, optical and mechanical characteristics of paper made from waste durian rinds fibre were investigated in this study. The durian rinds fibre pulp is produced through chemi-mechanical pulping. Naturally dried durian rinds from D24 variety were treated with 10% Sodium Hydroxide (NaOH) in room temperature for 2 hours and pulped by the refiner mechanical pulping (RMP) process. Durian rinds fibre pulp has been produced with four different beating times which are 0 PFI revolutions, 1000 PFI revolutions, 2000 PFI revolutions and 3000 PFI revolutions to investigate the effect of beating time. 3 stages Peroxide (PPP) TCF bleaching type was applied to 0 PFI revolutions pulps to investigate the effect of bleaching. 60 gsm type of paper were produced from durian rinds pulp to investigate the effect of beating and bleaching. Furthermore, 120 gsm paper also has been produced from durian rinds unbeaten pulp. Characteristics results show overall durian characteristics were increased with the effect of beating and TCF bleaching. The final ISO brightness has achieved 66.36% after stage 3 Peroxide treatment. 60 gsm durian rinds paper shows compatible characteristics with commercial scale paper produced by previous study. 120 gsm durian rinds fibre paper also have good characteristics to be implemented as raw material in liner paper and fluting medium for corrugated board. Experimental results show that durian rinds have great potential to be applied as non-wood raw material for commercial papermaking and become a value-added product.